2010
DOI: 10.1007/s12275-010-9262-2
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic evaluation of products inhibition to succinic acid producers Escherichia coli NZN111, AFP111, BL21, and Actinobacillus succinogenes 130ZT

Abstract: Succinic acid is one of the platform compounds and its production via natural feedstocks has drawn worldwide concerns. To evaluate the inhibitory effects of fermentation products on the growth of Actinobacillus succinogenes 130Z(T) and Escherichia coli NZN111, AFP111, BL21, fermentations with addition of individual products in medium were carried out. The cell growth was inhibited when the concentrations of formate, acetate, lactate, and succinate were at range of 8.8-17.6 g/L, 10-40 g/L, 9-18 g/L, and 10-80 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 28 publications
(28 reference statements)
1
14
0
Order By: Relevance
“…It was recently reported that E. coli strains NZN111, AFP111, and BL21 can tolerate up to 680 mM of succinate [32], a concentration similar to the predicted titer of the fast-growing strains, but much higher than the predicted titer of the slow-growing strains (Figure 6D). As such, it seems that this inhibitory effect will significantly reduce the consolidated performance of the slow-growing, high yield strains in some situations, making such strains less valuable.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…It was recently reported that E. coli strains NZN111, AFP111, and BL21 can tolerate up to 680 mM of succinate [32], a concentration similar to the predicted titer of the fast-growing strains, but much higher than the predicted titer of the slow-growing strains (Figure 6D). As such, it seems that this inhibitory effect will significantly reduce the consolidated performance of the slow-growing, high yield strains in some situations, making such strains less valuable.…”
Section: Resultssupporting
confidence: 57%
“…Based on the work of Li et al (2010) on four E. coli strains [32], we estimated S succ,* to be 80g/L or 678mM of succinate. k is a fitting parameter that determines that shape of the inhibition curve, which we assumed to be at 1.5.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the data in Figure 1 fall within the blue ‘data cloud’ and drastic growth inhibition is reflected by lower growth rates between 8 and 14 g.L −1 of SA. Surprisingly, the SA titre in Figure 1 does not correspond to the terminal SA titre when succinate is externally added prior to the fermentation [22,28]. In both these studies, growth was observed above SA titres of 30 g.L −1 indicating a difference between the influence of external and produced succinate on A. succinogenes .…”
Section: Introductionmentioning
confidence: 99%
“…10,11 AFP111 was a spontaneous glucose transporter (ptsG) mutation of NZN111, which produced succinate from glucose with a yield of nearly 0.9 mol mol −1 glucose containing only native genes. 12,13 Strain HL27659k was engineered by mutating succinate dehydrogenase (sdhAB), phosphotransacetylase (pta), acetate kinase (ackA), pyruvate oxidase (poxB), ptsG, and the isocitrate lyase repressor (iclR).…”
Section: Introductionmentioning
confidence: 99%